1998
DOI: 10.1046/j.1365-2559.1998.00413.x
|View full text |Cite
|
Sign up to set email alerts
|

Liver biopsy is a useful predictor of response to interferon therapy in chronic hepatitis C

Abstract: Liver biopsy provides useful information for selection of patients with hepatitis C for IFN therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
1

Year Published

2002
2002
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(46 citation statements)
references
References 38 publications
3
42
1
Order By: Relevance
“…Several studies have recently confirmed that the SVR [7] is impaired in patients with high body mass index and for those with hepatic steatosis. These data indicate that HCV carriers should avoid weight gain by diet and physical exercise before initiation of antiviral therapy, all efforts should be made to improve the metabolic steatosis of the patient.…”
Section: Insulin Resistancementioning
confidence: 91%
See 1 more Smart Citation
“…Several studies have recently confirmed that the SVR [7] is impaired in patients with high body mass index and for those with hepatic steatosis. These data indicate that HCV carriers should avoid weight gain by diet and physical exercise before initiation of antiviral therapy, all efforts should be made to improve the metabolic steatosis of the patient.…”
Section: Insulin Resistancementioning
confidence: 91%
“…When treating chronic hepatitis C (CHC), many clinicians do not take into consideration the presence of other comorbid conditions that lead to more progressive liver disease, such as cirrhosis and hepatocellular carcinoma (HCC) [3][4][5] . In recent studies, it has been proved that such comorbidities might reduce the response rate to PEGylated interferon (PEG-IFN)/ribavirin (RBV) therapy in HCV patients [6,7] . Eventually amelioration of these comorbidities before embarking on IFN-based therapy would improve the sustained virological response (SVR) and impair progression to cirrhosis and HCC.…”
Section: Introductionmentioning
confidence: 99%
“…8 The development of cirrhosis in patients with HCV may be associated with regression of steatosis, 21 as has previously been documented in non-alcoholic steatohepatitis (NASH). 22,23 The mechanisms leading to a reduction in steatosis in the liver with cirrhosis remain Mihm et al 99 Yes Ratziu et al 18 Yes Fartoux et al 19 Yes Czaja et al 9 Yes Yes Yes Hourigan et al 10,11 Yes Yes Yes Adinolfi et al 12 Yes Yes Yes Yes Westin et al 13 Yes Weak Yes Yes Castera et al 14 Yes Yes Monto et al 15 Yes Yes Yes Kumar et al 100 Yes Camps et al 101 Yes (BMI) Kaserer et al 102 Yes Bressler et al 60 Yes (BMI) Rubbia-Brandt et al 28 Yes Yes Poynard et al 16 Yes Yes Yes Yes Yes Patton et al 17 Yes Yes Yes Yes Yes Nair et al 70 No* Marrero et al 103 Yes Ohata et al 74 Yes *Steatosis was a risk for HCC in alcoholic and cryptogenic cirrhosis only. Abbreviation: BMI, body mass index.…”
Section: Steatosis Influences the Progression Of Fibrosis In Chronic Hcvmentioning
confidence: 99%
“…Further more, hyperleptinemia in obese is an independent risk factor for non-response to antiviral therapy [74] . Hyperferritinemia downregulates the response to interferon therapy [75,76] . From this review, we have noted that steatosis, either metabolic or cytopathic, contributes to the development of NASH and progression to fibrosis, cirrhosis and HCC.…”
Section: Response To Interferon Therapy In Hcv Infectionmentioning
confidence: 99%